Innovative behavior of family farmers in Brazil in the face of innovations in the agricultural sector - Luis Felipe Dias Lopes; Silvana Bortoluzzi Balconi; Raquel Dalvit Flores; Martiele Gonçalves Moreira; Deoclécio Junior Cardoso da Silva; Rayssa Cleide de Oliveira; Daniela Pegoraro; Gilnei Luiz de Moura; Daniel Knebel Baggio; Adriane Fabricio; Joana Vieira dos Santos (Economia Agro-Alimentare)
Innovation in family farming plays a critical role in regional economic and social development by introducing new products, technologies, processes, and attitudes. This article aims to evaluate the innovative behaviors of family farmers in southern Brazil concerning agricultural sector innovations. We conducted a quantitative survey of 442 family farmers, employing partial least squares structural equation modeling and multigroup analysis as our analytic methods. Our results reveal both direct and indirect relationships among the dimensions of the innovative behavior scale, tailored to family farming, and the moderating role of organic production on the model. Comparative analysis showed no significant difference in the intensity of the dimensions between organic producers and nonproducers. This study offers valuable insights into innovative behavior in family farming, which could inform strategic planning and more effectively direct public policies to support family farmers, ultimately leading to technological advancement and innovation within the sector.